Measurements of Small Field Output Correction Factors on a RefleXion Treatment Machine - Weili Zhong; Zhe (Jay) Chen; Min‐Young Lee; Fada Guan; Huixiao Chen; Dae Yup Han (Precision Radiation Oncology)
Abstract Purpose The response of various detectors in small fields from a variety of treatment machines has been studied and is summarized in IAEA TRS‐483. However, data for the novel RefleXion system remains largely unexplored. This study measured the output correction factors of multiple detectors in small fields for a clinical RefleXion unit. Methods The RefleXion machine consists of a binary multi‐leaf collimator and two pairs of Y‐jaws with clinical openings of 1 and 2 cm. The reference dosimetry is applied to the 10 × 2 cm2 clinical‐reference field, and the output factors of different fields are presented relative to the clinical‐reference field. The responses of detectors Edge, Razor, Micro‐Diamond, A14SL, CC01 and CC03 in rectangular fields from 1.25 × 1 to 20 × 2 cm2 on the RefleXion unit was studied at a depth of 10 cm in an IBA Blue‐Phantom‐Helix with a 85 cm source‐to‐surface distance. Gafchromic EBT4 film data in a solid‐water phantom were used as the reference to obtain correction factors for the detectors. Results In the fields of the 2 cm jaw, all 6 detectors showed similar responses to the film reference within around 0.5% except at the first field width (1.25 cm), where the Edge and Micro‐Diamond exhibited over‐response and the CC13 showed the volume effect of ion chambers. In the fields of the 1 cm jaw, the Edge and Micro‐Diamond had responses close to the film and the same over‐response at small field‐widths. Significant deviations of the CC13 (∼4%) and the A14SL (∼2.5%) from the film were present over the whole range of field widths. Conclusions The small field output correction factors of 6 kinds of detectors were determined for a RefleXion system, conforming to the formalism in TRS‐483. All detectors except CC13 fulfil the 5% correction limit recommended by the TRS‐483 for output factor measurement.